CHAC1 Mediates Endoplasmic Reticulum Stress‐Dependent Ferroptosis in Calcium Oxalate Kidney Stone Formation - Caitao Dong; Ziqi He; Wenbiao Liao; Qinhong Jiang; Chao Song; Qianlin Song; Xiaozhe Su; Yunhe Xiong; Yunhan Wang; Lingchao Meng; Sixing Yang (Advanced Science)
Abstract The initiation of calcium oxalate (CaOx) kidney stone formation is highly likely to stem from injury to the renal tubular epithelial cells (RTECs) induced by stimulation from an aberrant urinary environment. CHAC1 plays a critical role in stress response mechanisms by regulating glutathione metabolism. Endoplasmic reticulum (ER) stress and ferroptosis are demonstrated to be involved in stone formation. This study attempted to elucidate the mechanism of ER stress‐dependent ferroptosis and the role of CHAC1 in CaOx kidney stones. Here, regulating ER stress and CHAC1 expression are performed in in vivo and in vitro stone models. These findings indicated that 4‐Phenylbutyric acid (4‐PBA)treatment and CHAC1 deficiency alleviated the ferroptotic status, including restoring GSH content, suppressing Fe2+ and lipid peroxidation accumulation, as well as regulating ferroptosis‐related proteins. Notably, 4‐PBA treatment and CHAC1 deficiency both attenuated oxidative damage, improved renal function, importantly, decreased crystal deposition. Additionally, ChIP‐seq and ChIP‐qPCR analyses demonstrated that CHAC1 is the vital downstream target gene of ATF4. The results indicated that ATF4 depletion inhibited the upregulation of CHAC1 and pro‐ferroptotic response induced by Ox stimulation. Overall, ATF4/CHAC1 axis mediating ER stress‐dependent ferroptosis may be a promising research direction for identifying potential strategy to prevent and treat CaOx kidney stones.